Legal Counselling Regarding Law Enforcement on Violence Against Women and Children and Financial Literacy For Women at Sekolah Perempuan Srikandi in Dauh Puri Kaja Village, Denpasar, Bali - Putu Eka Trisna Dewi; Luh Riniti Rahayu; Sri Sulandari; Ayu Putu Utari Parthami Lestari (Fakultas Hukum, Universitas Warmadewa, 2024)
Indonesia has been the site of a number of incidents involving violence and discrimination that have attracted significant attention. Indeed, the number of such cases is on the rise. The prevalence of discrimination against women is influenced by a number of factors, one of which is economic. Protection of women is of paramount importance in order to safeguard women’s rights from discrimination. The protection of women’s rights can be effectively achieved through the promotion of women’s empowerment and the encouragement of their active participation in the political and social spheres. This will facilitate the reduction of gender-based discrimination and violence. The establishment of Sekolah Perempuan Srikandi represents a significant advancement in the effort to address violence against marginalised women and children. A complaint centre for violence against women and children has been established in Dauh Puri Kaja Village, Denpasar. Nevertheless, it is evident that members of Sekolah Perempuan Srikandi who establish the women’s and children’s violence complaint centre require legal guidance during the initial stages of their operations. It is therefore crucial that legal counsel is made available at the school in order to educate and inform women of the legal steps involved in law enforcement and financial literacy. Women represent an element of family economic support that is susceptible to legal issues, and thus the phenomenon is addressed through the Community Service Programme by Ngurah Rai University.